NOMENKLATUR BIDANG KEBUDAYAAN DI PEMERINTAH PROVINSI: BERGABUNG DENGAN BIDANG PENDIDIKAN ATAU BIDANG PARIWISATA? - Setiawan, Budiana (Kebudayaan, 2016)
AbstractCulture sector, which was transferred into the Ministry of Culture and Tourism since2001, was back to the Ministry of Education and Culture in October 2011. The changes oforganizational structure in ministerial level should be followed by changes of organizationalstructure in officials in provincial level. But in reality, the majority of provincial governmentsretain the culture sector together with tourism sector. This case provokes a question why thechange of organizational structure in the ministerial level is not followed by most of the officialsin provincial level. The method of this study is literature study of some articles and essays frombooks and internets, which contain history of culture sector in ministerial level, role of culturefor tourism, role of culture for education, as well as examples of official that manages culturesector in three provinces (West Kalimantan, West Sumatra, and Yogyakarta Special Region). Theresults shows that many officials merge culture sector together with tourism sector because themeaning of culture sector is considered to have a stronger synergy with tourism than education.The provincial government considers that culture sector needs to be empowered for the benefitof tourism sector. Conversely, tourism development will strengthen people’s culture in theirprovinces. Culture-based tourism development will also increase local income for the province AbstrakBidang kebudayaan yang sejak tahun 2001 bergabung dalam Kementerian Kebudayaandan Pariwisata, mulai Oktober 2011 beralih kembali ke Kementerian Pendidikan danKebudayaan. Perubahan struktur organisasi di tingkat kementerian tersebut semestinya diikutidengan perubahan struktur organisasi kedinasan di tingkat pemerintahan provinsi. Namundalam kenyataannya sebagian besar dinas di tingkat provinsi tetap mempertahankan bidangkebudayaan disatukan dengan bidang pariwisata. Hal ini menimbulkan pertanyaan, mengapaperubahan struktur organisasi di tingkat kementerian tersebut tidak diikuti oleh sebagian besardinas di tingkat provinsi? Metode yang digunakan dalam kajian ini adalah dengan melakukanstudi pustaka terhadap tulisan-tulisan dan laman-laman, yang memuat tentang sejarah bidangkebudayaan di tingkat kementerian, peran kebudayaan terhadap pariwista, peran kebudayaanterhadap pendidikan, serta contoh-contoh dinas yang menangani bidang kebudayaan di tigaprovinsi (Kalimantan Barat, Sumatera Barat, dan D.I. Yogyakarta). Hasil kajian menunjukkanbahwa hal tersebut disebabkan pemaknaan bidang kebudayaan yang dianggap lebih bersinergidengan pariwisata daripada pendidikan. Pemerintah provinsi memandang bidang kebudayaandapat diberdayakan untuk kepentingan bidang pariwisata. Sebaliknya, pengembangan pariwisataakan memperkokoh kebudayaan masyarakat di provinsi tersebut. Perkembangan pariwisatayang berbasis kebudayaan juga akan meningkatkan Pendapatan Asli Daerah (PAD) bagi provinsitersebut.